O7 T1ρ magnetic resonance imaging of the talar cartilage in individuals with & without chronic ankle instabiltiy. (17th September 2017) - Song, K; Pietrosimone, BG; Wikstrom, EA
Abstract : Study Design: Case control study. Objectives: To determine if chronic ankle instability (CAI) patients have lower proteoglycan density (PGD) in their talar cartilage compared to the uninjured controls. Background: Recurrent ankle injuries are a leading cause of ankle post-traumatic osteoarthritis (PTOA). PGD is responsible for the high elasticity and resilience of the tissue and decreased PGD measured with T1ρ MRI may be an early indicator of PTOA, but PGD has not been examined in CAI patients. Methods and Measures: 9 CAI and 9 controls participated. T1ρ MRI was performed using a Siemens Magnetom TIM Trio 3T scanner. Participants were non-weight bearing for 30 min prior to the scan to unload the cartilage. The involved CAI limb and dominant limb for controls were scanned. Segmentation of the talar cartilage was performed with T1ρ MRI images acquired during the 0 ms spin lock duration using ITK-SNAP software. Four regions of interest (ROI): anteriomeidal (AM), anteriolateral (AL), posteriomedial (PM), and posteriolateral (PL) were identified during segmentation. Voxel by voxel T1ρ relaxation times were calculated from a five-image sequence created with a custom Matlab program. Mean T1ρ relaxation times, an indicator of PGD, in each ROI were compared between CAI patients and healthy controls using independent t-tests. Results: Significant T1ρ relaxation time differences (p=0.015) in the PL ROI in CAI patients (67.66±5.87 ms) compared to controls (60.59±5.10 ms). Despite higher relaxation times in CAI patients (AM:67.92±7.11 ms, AL:68.20±6.66 ms, PM:68.63±6.99 ms) no differences were noted (AM: p=0.920, AL: p=0.131, PM: p=0.086) compared to controls (AM:67.57±7.12 ms, AL:63.57±5.62 ms, PM:63.33±5.18 ms). Conclusions: CAI patients showed higher T1ρ relaxation times compared to controls suggesting reduced PGD in the talar cartilage. This finding supports the existing arthroscopic literature that illustrates early degenerative changes in CAI patients. Further research is needed to determine therapeutic interventions that can improve measures of cartilage health by improving ankle joint biomechanics.